The Correlation between Dietary Pattern with the Prevalence and Degree of Depression in Female Students of SMAK St. Louis Surabaya - Kezia Eirene Simanjuntak; Sri Umijati; Nining Febriyana; Yunias Setiawati (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: The increasing prevalence of depression and irregular dietary pattern amongst adolescent, especially women, has become an important issue today. A number of studies confirm that dietary pattern plays a role as one of the biological factors affecting mood regulation through the production of nerotransmitters, however, there are conflicting results regarding the matter in adolescent. This study aimed to examine the correlation between dietary pattern and depression in adolescent. Methods: This study was done through cross sectional analytical observational study in 89 high school students in SMAK St. Louis Surabaya. The data was gathered through two types of questionnaires filled by the respondents. The questionnaires were Food Frequency Questionnaire to assess dietary intake pattern and Beck Depression Inventory to assess the occurence of depression amongst the respondents. Results: The study showed high prevalence of irregular dietary pattern and depression within the sample. From Spearman correlation test, there is no correlation between dietary pattern and the prevalence as well as the degree of depression (p > 0,05). Conclusion: There is no correlation between dietary pattern and depression in adolescent. It may be caused by a lot of other factors contributing to the occurence of depression, including biological, psychological, and social factors.